Development of an immunochromatographic lateral flow strip for the simultaneous detection of aminoglycoside residues in milk. Issue 17 (5th March 2018) - Sun, Yaning; Yang, Jifei; Yang, Suzhen; Sang, Qingbo; Teng, Man; Li, Qingmei; Deng, Ruiguang; Feng, Lili; Hu, Xiaofei; Zhang, Gaiping
Abstract : A colloidal gold-based immunochromatographic strip has been developed for the rapid, simultaneous, semi-quantitative and quantitative detection of several aminoglycoside residues in milk, including gentamicin sulfate (GM), neomycin sulfate (NEO) and kanamycin sulfate (KN). Abstract : A colloidal gold-based immunochromatographic strip with a competitive format has been developed for the rapid, simultaneous, semi-quantitative and quantitative detection of several aminoglycoside residues in milk, including gentamicin sulfate (GM), neomycin sulfate (NEO) and kanamycin sulfate (KN). Three monoclonal antibodies against the three corresponding aminoglycosides were conjugated to colloidal gold particles and applied to the conjugate pads of the strip. The competitors [GM-bovine serum albumin (GM-BSA), NEO-BSA and KN-BSA conjugates] of GM, NEO and KN were immobilized onto a nitrocellulose (NC) membrane at three detection zones, T1, T2, and T3, respectively. The minimal cut-off values of the strip were 10 ng mL −1 for GM, and 100 ng mL −1 for NEO and KN, which are lower than the maximum residue levels (MRLs) established for aminoglycosides. The IC50 values of the strip were 0.737 ng mL −1, 8.971 ng mL −1 and 11.110 ng mL −1 for GM, NEO and KN respectively. In conclusion, the immunochromatographic lateral flow strip could be used for rapid, simultaneous, semi-quantitative and quantitative detection of GM, NEO and KN residues in milk.